# Let U = {1,

Given that

U = {1, 2, 3, 4, 5, 6, 7, 8, 9}

A = {1, 2, 3, 4}

B = {2, 4, 6, 8}

C = {3, 4, 5, 6}

(i) We have to find complement of A, which is given by (U - A)

A’ = U - A

A’ = {1, 2, 3, 4, 5, 6, 7, 8, 9} - {1, 2, 3, 4}

A’ = {5, 6, 7, 8, 9}

(ii) B’ = U - B

B’ = {1, 2, 3, 4, 5, 6, 7, 8, 9} - {2, 4, 6, 8}

B’ = {1, 3, 5, 7, 9}

(iii) (A C)’ = U - (A C)

First we find (A C)

(A C) = {1, 2, 3, 4} {3, 4, 5, 6}

(A C) = {1, 2, 3, 4, 5, 6}

Now,

(A C)’ = U - (A C)

(A C)’ = {1, 2, 3, 4, 5, 6, 7, 8, 9} - {1, 2, 3, 4, 5, 6}

(A C)’ = {7, 8, 9}

(iv) (A B)’ = U - (A B)

First we find (A B),

(A B) = {1, 2, 3, 4} {2, 4, 6, 8}

(A B) = {1, 2, 3, 4, 6, 8}

Now,

(A B)’ = U - (A B)

(A B)’ = {1, 2, 3, 4, 5, 6, 7, 8, 9} - {1, 2, 3, 4, 6, 8}

(A B)’ = {5, 7, 9}

(v)We want to find complement of A’, which is given by U - A’

From part (i), we have A’ = {5, 6, 7, 8, 9}

(A’)’ = U - A’

(A’)’ = {1, 2, 3, 4, 5, 6, 7, 8, 9} - {5, 6, 7, 8, 9}

(A’)’ = {1, 2, 3, 4} = A

We conclude that (A’)’ = A.

(vi) (B - C)’ = U - (B - C)

First we find (B - C),

(B - C) = {2, 4, 6, 8} - {3, 4, 5, 6}

(B - C) = {2, 8}

Now,

(B - C)’ = U - (B - C)

(B - C)’ = {1, 2, 3, 4, 5, 6, 7, 8, 9} - {2, 8}

(B - C)’ = {1, 3, 4, 5, 6, 7, 9}

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Prove that A <spaRS Aggarwal - Mathematics

if U = {a, b, c} RS Aggarwal - Mathematics

For any two sets RD Sharma - Mathematics

For any two sets RD Sharma - Mathematics

For any two sets RD Sharma - Mathematics

If A, B, C are thRD Sharma - Mathematics

For any two sets RD Sharma - Mathematics

For any two sets RD Sharma - Mathematics

For any two sets RD Sharma - Mathematics

For any two sets RD Sharma - Mathematics